2004
DOI: 10.1159/000083611
|View full text |Cite
|
Sign up to set email alerts
|

Receptors to Steroid Hormones and Aromatase Are Expressed by Cultured Motoneurons but Not by Glial Cells Derived from Rat Embryo Spinal Cord

Abstract: The aim of this study was to examine the expression of aromatase and receptors to steroid hormones in cultured motoneurons (MNs). We first developed an original method for obtaining rat MN cultures. Dissociated E15 rat spinal cords were purified using metrizamide and bovine serum albumin density gradients, and cells were then seeded on the culture substratum. We optimized the culture parameters and found that simple addition of rat muscle extract (ME) and conditioned culture medium (CM) from glial cell lines (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 132 publications
1
21
1
Order By: Relevance
“…This neuroprotective activity of 17b-estradiol was not modified by the estrogen receptor antagonist ICI 182,780 added directly to the astrocyte-motor neuron co-culture during the 24 h of damage development, thus ruling out an interaction of the hormone with neuronal estrogen receptor. In addition, despite the recently reported expression of estrogen receptors on cultured spinal cord motor neurons [Rakotoarivelo et al, 2004], we have not been able to detect any protective activity when 17b-estradiol was added directly to motor neurons exposed to AMPA [Platania et al, 2005].…”
Section: Amyotrophic Lateral Sclerosis (Als)contrasting
confidence: 93%
“…This neuroprotective activity of 17b-estradiol was not modified by the estrogen receptor antagonist ICI 182,780 added directly to the astrocyte-motor neuron co-culture during the 24 h of damage development, thus ruling out an interaction of the hormone with neuronal estrogen receptor. In addition, despite the recently reported expression of estrogen receptors on cultured spinal cord motor neurons [Rakotoarivelo et al, 2004], we have not been able to detect any protective activity when 17b-estradiol was added directly to motor neurons exposed to AMPA [Platania et al, 2005].…”
Section: Amyotrophic Lateral Sclerosis (Als)contrasting
confidence: 93%
“…Sex steroids can be synthesized in a number of tissues, including the central nervous system [56]. In the spinal cord, enzymes in the biosynthetic pathway for androgens are found both in motoneurons [57], [58] and glial cells [59], [60], [61], [62], indicating that these cells could be a source of localized production of androgens. Of particular interest is the enzyme cytochrome C P450 aromatase, which catalyzes the conversion of testosterone and its precursors into estradiol, a potent neurosteroid.…”
Section: Discussionmentioning
confidence: 99%
“…This gestational period is thought to be when masculinization of the GFN occurs [3], as it is when flutamide inhibits inguinoscrotal TD [8]. Some studies have found AR in the motor neurons of E rats [10,11]. In addition, AR messenger RNA has been isolated in the spinal cord and DRG of E male mice [12]; however, this did not include protein expression.…”
Section: Discussionmentioning
confidence: 99%